Global meta‐analysis of how marine upwelling affects herbivory. Issue 2 (6th November 2019) - Sellers, Andrew J.; Leung, Brian; Torchin, Mark E.
Abstract: Aim: Nutrient subsidies support high primary productivity, increasing herbivore abundance and influencing their top‐down control of producers. Wind‐driven upwelling events deliver cold nutrient‐rich water to coastlines, supporting highly productive marine environments. Results from studies comparing ecological processes across upwelling regimes are mixed: some reveal weaker herbivory in upwelling regions, while others report a positive relationship between upwelling and herbivory. In this synthesis we examine the influence of upwelling on top‐down control of producers across the globe. Location: Global; marine ecosystems. Time period: 1978–2017. Major taxa studied: Marine herbivores and algae. Methods: We used data from herbivory studies focusing specifically on the influence of upwelling activity (upwelling studies), and a broader collection of herbivore exclusion studies dating back four decades. For the upwelling studies we compared herbivore effects between experiments replicated across sites for which upwelling conditions were described by the authors. Meanwhile, for the broader collection of experiments we used externally sourced oceanographic data to characterize upwelling activity, and examined how herbivory changed along a gradient of upwelling activity. Results: Our results consistently reveal that upwelling weakens herbivore effects on producers. Herbivory was, on average, four times weaker in upwelling sites relative to sites under weak upwelling or downwelling regimes in studies that specifically examined upwelling. The analysis of the broader herbivory literature revealed a similar weakening influence of upwelling on herbivory; however, the effect size was smaller and varied across producer functional groups. Main conclusions: Nutrient subsidies from upwelling events reduce top‐down control by herbivores in coastal ecosystems; however, the negative relationship between upwelling intensity and herbivory is likely the result of a combination of co‐occurring processes. First, increased primary production overwhelms consumption by herbivores. Second, cold water reduces herbivore metabolism and activity. Finally, surface currents associated with upwelling activity transport herbivore larvae offshore, decoupling secondary production from herbivory.